Promotion Activities for Curug Rahong Tourism Village to Boost Tourists Arrival - Retno Dyah Kusumastuti; Fathinah Ranggauni Hardy; Muhammad Ikhsan Amar (International Journal of Business Studies, 2020)
This study focuses on the promotion activities in Curug Rahong Tourism Village. Curug Rahong Tourism Village is one of the recently established tourism village that is located in Pandeglang Regency, Province of Banten. The objective of this study is explore further about promotional activities that has been done by Curug Rahong Tourism Village management. This study is a descriptive study with qualitative approach, and the data for this study was collected using observation, interview, and documentation. This study finds that Curug Rahong Tourism Village promotion activities were carried out using promotional tools in the form of advertisements, word of mouth, and interactive marketing. Curug Rahong Tourism Village Manager advertises using brochures, while interactive marketing is done through websites and a number of social media platforms, namely Facebook and Instagram. As for the implication, this study suggests that it is important for the management of tourism village to utilize the internet as tool of promotion, innovate the offerings to the tourists, and raise the awareness of the local community about the importance of tourism itself.